Endoscopy-Assisted Total Mastectomy with and without Immediate Reconstruction: An Extended Follow-Up, Multicenter Study. Issue 2 (29th October 2020) - Kuo, Yao-Lung; Chang, Chih-Hao; Chang, Tzu-Yen; Chien, Hsiung-Fei; Liao, Li-Min; Hung, Chin-Sheng; Lin, Shih-Lung; Chen, Shou-Tung; Chen, Dar-Ren; Lai, Hung-Wen
Abstract : Background: Endoscopy-assisted total mastectomy has been used for surgical intervention of breast cancer patients; however, large cohort studies with long-term follow-up data are lacking. Methods: Breast cancer patients who underwent endoscopy-assisted total mastectomy from May of 2009 to March of 2018 were collected prospectively from multiple centers. Clinical outcome, impact of different phases, oncologic results, and patient-reported aesthetic outcomes of endoscopy-assisted total mastectomy were reported. Results: A total of 436 endoscopy-assisted total mastectomy procedures were performed; 355 (81.4 percent) were nipple-sparing mastectomy, and 81 (18.6 percent) were skin-sparing mastectomy. Three hundred fourteen (75.4 percent) of the procedures were associated with immediate breast reconstruction; 255 were prosthesis based and 59 were associated with autologous flaps. The positive surgical margin rate for endoscopy-assisted total mastectomy was 2.1 percent. In morbidity evaluation, there were 19 cases (5.4 percent) with partial nipple necrosis, two cases (0.6 percent) with total nipple necrosis, and three cases (0.7 percent) with implant loss. Compared with the early phase, surgeons operating on patients in the middle or late phase had significantly decreased operation time and blood loss. With regard to patient-reported cosmetic outcomes, approximately 94.4 percent were satisfied with the aesthetic results. Patients who underwent breast reconstruction with preservation of the nipple had higher satisfaction rates. Over a median follow-up of 54.1 ± 22.4 months, there were 14 cases of locoregional recurrence (3.2 percent), three distant metastases (0.7 percent), and one mortality (0.2 percent). Conclusion: This multicenter study showed that endoscopy-assisted total mastectomy is a reliable surgical intervention for early breast cancer, with high patient satisfaction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.